O ensino de história das Áfricas na Universidade do Estado de Santa Catarina (1998-2013) - Silva, Mariana Heck (2017)
The present work aims to reflect on what has been taught in the disciplines of History of Africa I and II in the undergraduate course in History at the State University of Santa Catarina, Brazil. The time cut of our study starts from 1998, when the discipline of History of Africa I was taught for the first time, until 2013, when federal law 10.639, which makes compulsory the teaching of this subject, has completed 10 years. Our analysis were made relating the teachers' choices as well as the perspectives built by the students from their places of enunciation. We consider that these places are surrounded by racial, gender, sexual orientation, social movements and academic formation issues that influence In the way people resignify and perceive the world around them. The purpose was to understand the ways taken by the teachers in the construction of the disciplines, passing theoretical, methodological and content choices. Besides, we aimed to analyse the perspectives created by the students from these choices. The sources of this research include institutional documents of the university, the undergraduate course of History and the disciplines of History of Africa I and II, as well as curricula, interviews and bibliographic productions of teachers and questionnaires applied to the students